Filipino As Second Language: Guide In Acquiring Filipino By Reading Novels - Hernando L. Bernal Jr.; Renz Chester R. Gumaru; Sammy T. Oleo (RIRAI Publisher, 2020)
Learning a second language is one thing. Learning a second language through reading a text is another thing. This study aims to show the acquisition of Filipino as Second Language of the respondents who are reading novels. The researcher utilized the Descriptive Method of research with the questionnaire as the main data-gathering instrument since this study focused on Reading Filipino Novels in Acquiring Filipino as Second Language; Basis in Designing a Guide to Enhance Filipino Proficiency. Engaging children in reading novels have some effects on how they acquire new language. The improvement of a child is not only about himself but also there are some factors concerning it.This study aims to show the acquisition of Filipino as Second Language of the respondents who are reading novels. Those respondents who are fond of reading such novels will acquire something